Mechanism of altruism approach to blood donor recruitment and retention: a review and future directions. Issue 4 (27th August 2015) - Ferguson, E.
SUMMARY Why do people donate blood? Altruism is the common answer. However, altruism is a complex construct and to answer this question requires a systematic analysis of the insights from the biology, economics and psychology of altruism. I term this the mechanism of altruism (MOA) approach and apply it here for understanding blood donor motivation. The answer also has enormous implications for the type of interventions we choose to adopt as a society. A MOA approach so far shows that blood donors are a mixture of (i) warm‐glow givers (donation is emotionally rewarding) and (ii) reluctant altruists (cooperate rather than defect when free‐riding is high). Donors also show 'saintly sinning' with the extra 'moral currency' form blood donation allowing them to be less generous in other contexts. The MOA approach suggests why financial incentives, in terms of gifts/lottery tickets, are effective and suggests a number of novel interventions for donor recruitment: 'voluntary reciprocal altruism' and 'charitable incentivisation'. The MOA approach also highlights the need for an intervention developed specifically for recipients to allow them to show their gratitude to donors and for society to celebrate blood donation. It is suggests a 'Monument to Blood Donors' will achieve this. The approach suggests a number of novel research questions into (i) donor self‐selection effects, (ii) conditional cooperation and (iii) construct overlap with Theory of Planned Behaviour (e.g. affective attitudes and warm‐glow). The MOA offers a powerful way to understand blood donor motivations around altruism and develop theoretically driven interventions.